Cervix Cancer Research Network (CCRN): Improving Access to Cervix Cancer Trials on a Global Scale. Issue 9 (1st November 2016) - Gaffney, David; Small, Bill; Kitchener, Henry; Young Ryu, Sang; Viswanathan, Akila; Trimble, Ted; Covens, Al; Wilailak, Sarikapan; Lertkhachonsuk, Arb-aroon; Sitathanee, Chomporn; Mahantshetty, Umesh; Fisher, Brandon; et al.
Abstract : Abstract: Eighty-seven percent of cervix cancer occurs in less-developed regions of the world, and there is up to an 18-fold difference in mortality rate for cervix cancer depending on the region of the world. The Cervix Cancer Research Network (CCRN) was founded through the Gynecologic Cancer InterGroup with the aim of improving access to clinical trials in cervix cancer worldwide, and in so doing improving standards of care. The CCRN recently held its first international educational symposium in Bangkok. Sixty-two participants attended from 16 different countries including Pakistan, India, Bangladesh, Thailand, Malaysia, Singapore, Philippines, Taiwan, China, Vietnam, Korea, Japan, Columbia, Brazil, Canada, and the United States. The focus of this symposium was to evaluate progress, to promote new clinical trials for the CCRN, and to provide education regarding the role of brachytherapy in the treatment of cervical cancer.